The Relationship Between Knowledge Levels and Social Support For the Implementation of the Covid-19 Vaccine at STIKES Harapan Ibu Jambi: Hubungan Tingkat Pengetahuan Dan Dukungan Sosial Terhadap Pelaksanaan Vaksin Covid-19 di STIKES Harapan Ibu Jambi - Ayu Nopita; Dasukii; Ani Astuti (Caring : Jurnal Keperawatan, 2022)
One of the Indonesian government's efforts to prevent the spread of COVID-19, but the target for implementing the vaccine has not yet met the national target. Factors that influence it are knowledge and social support. This study aims to clarify the relationship between the level of knowledge and social support for the implementation of the covid-19 vaccine. This research uses quantitative research with cross sectional research design. The sample population in this study were all employees of STIKES Harapan Hawa Jambi in 2021, totaling 76 people using the total sampling method. This research was carried out on August 3 to August 11, 2021 at STIKES Harapan Ibu Jambi. The instrument used is a questionnaire sheet. The data obtained were analyzed by univariate and bivariate using chi-square test. The results of the univariate analysis showed that there were 52 (68.4%) respondents who had knowledge in the good category, there were 47 (61.8%) respondents who had social support in the good category and there were 67 (88.2%) respondents who took the covid-19 vaccine. in the positive category at STIKES Harapan Ibu Jambi in 2021. Bivariate analysis shows that there is a relationship between knowledge (p=0.000) and social support (p=0.025) in administering the covid-19 vaccine. It can be concluded that knowledge and social support are related to the implementation of the covid-19 vaccine